Refining the selection of patients with metastatic colorectal cancer for treatment with temozolomide using proteomic analysis of O6-methylguanine-DNA-methyltransferase. (January 2019) - Schwartz, Sarit; Szeto, Chris; Tian, Yuan; Cecchi, Fabiola; Corallo, Salvatore; Calegari, Maria Alessandra; Di Bartolomeo, Maria; Morano, Federica; Raimondi, Alessandra; Fucà, Giovanni; Martinetti, Antonia; De Pascalis, Ivana; et al.
Abstract: Background: The repair enzyme O6-methylguanine-DNA-methyltransferase (MGMT) is a validated predictor of benefit from temozolomide (TMZ) in glioblastoma. However, only 10% of patients with MGMT -methylated metastatic colorectal cancer (mCRC) respond to TMZ. Methods: Archived tumour samples (N = 41) from three phase II TMZ trials carried out in MGMT -methylated mCRC (assessed by methylation-specific polymerase chain reaction [PCR]) were stratified by MGMT status as assessed by three different methods: mass spectrometry, PCR/methyl-BEAMing and RNA-seq. The performance of each method was assessed in relation to overall response rate, progression-free survival (PFS) and overall survival (OS). Results: Overall, 9 of 41 patients responded to TMZ. Overall response rates were 50% (9/18), 50% (6/12) and 35% (8/23) among patients determined likely to respond to TMZ by mass spectrometry, methyl-BEAMing and RNA-seq, respectively. Low/negative MGMT protein expressors by mass spectrometry had longer PFS than high MGMT expressors (3.7 vs 1.8 months; HR = 0.50, P = 0.014). Results for OS were similar but statistically non-significant (8.7 vs. 7.4 months; HR = 0.55, P = 0.077). No significant association between survival and MGMT status by methyl-BEAMing or RNA-seq could be demonstrated as comparable subgroups survival could not be confirmed/excluded. Specifically, the association of high versus low methyl-BEAMing MGMT hypermethylation with survival was HR = 0.783, P = 0.46 for PFS and 0.591, P = 0.126 for OS, while association of low versus high RNA-seq MGMT level with survival was HR = 0.697, P = 0.159 for PFS and HR = 0.697, P = 0.266 for OS. Conclusions: Quantitative proteomic analysis of MGMT may be useful for refining the selection of patients eligible for salvage treatment with single-agent TMZ. Highlights: 10% O6-methylguanine-DNA-methyltransferase (MGMT)-methylated metastatic colorectal cancers respond to temozolomide (TMZ). 50/50/35% responses for MGMT selection with mass spectrometry/methyl-BEAMing/RNA-seq. Mass spectrometry: 100% sensitivity/50% specificity/80% accuracy for response to TMZ. Low/negative MGMT protein expression was significantly associated with longer progression-free survival. Quantitative proteomic MGMT analysis could refine patients' selection for TMZ.